AB0341 How common is discordance in das components in patients with rheumatoid arthritis. (15th June 2017) - Shaikh, M
Abstract : Background: Chronic pain remains a significant problem for patients with rheumatoid arthritis (RA) despite advances in the management of joint inflammation (1–3). Pain that persists in the absence of significant inflammatory disease activity is thought to arise from sensitisation of the central nervous system. Composite scores such as DAS28, combine both objective and subjective aspects of disease. This may overestimate inflammatory disease in patients in whom pain occurs independently and has implications for treatment. However, the proportions of patients with such discordance is not clear. Objectives: 1. To assess the degree of discordance between objective and subjective components of the DAS28 score in patients attending rheumatology clinics in a teaching hospital in Cambridge. 2. To assess the association between such discordance and the DAS28-P measure Methods: A retrospective review of clinic notes was conducted of patients attending the rheumatology department at Addenbrooke's Hospital, Cambridge. Patients attending the early arthritis clinic, nurse practitioner follow up clinic and biologics clinic were included. Demographic information was collected including age, gender, current use of synthetic and biologic DMARDs. DAS28 scores and the individual components were retrieved and analysed. DAS28P was calculated as well as the difference between tender and swollen joint count (TJC-SJC) which has also been noted to be a measure of discordance between subjective and objective symptoms. Results: 120 patients with RA were studied. The mean age was 59.4 years (range 27–86). 74% (89) were female. 88% (106) were on synthetic DMARDs: MTX 48% (58), HCQ 37% (45), SSZ 12% (15), LEF 3% (4), Gold 0.8% (1). 30% (36) were on biologic DMARDs: RTX 30% (11), ETA 30% (11), TOCI 17% (6), ADA 14% (5), ABA 6% (2). Mean DAS28 was 3.42, SD 1.39. Mean TJC 4, mean SJC 2. Mean PGA 43, SD 24. DAS28-P was calculated as per previous studies (3). Mean TJC-SJC was 2, median 1. PGA and TJC-SJC (r=0.33) and TJC-SJC and DAS28P were correlated (r=0.44). Conclusions: Discordance between subjective and objective components of DAS scores is relatively frequent in patients with RA. This can lead to confounding of DAS scores. There is currently no formal system of assessing the degree of such discordance which can have implications for treatment of inflammatory disease as compared to pain management strategies. References: Taylor, P. et al., 2010. J. Int. Med. Res. 38, 1213–1224. Strand, V. et al., 2015. J. Rheumatol. 42, 2046–2054. McWilliams, D.F. et al., 2012. Arthritis Care Res. 64, 1505–1513. Disclosure of Interest: None declared